C-reactive protein and thrombocytopenia as essential early indicators: Subtle approach to neonatal sepsis - Ruchi Kotpal; Sonal Jindal (Journal of Family Medicine and Primary Care, 2024)
Introduction: Early diagnosis of neonatal sepsis is very essential part of newborn care to prevent mortality and decrease morbidity in newborns. Aim: The aim of this study is to correlate an increase in C-reactive protein (CRP) titre and a decrease in platelet count with an increased incidence of neonatal septicemia, for an effective subtle approach in neonatal septicemia. Materials and Methods: A retrospective study was conducted in the neonatal intensive care unit (NICU) of a tertiary care hospital from Jan 2022 to July 2023. Neonates admitted to the NICU with suspected sepsis were screened for sepsis. Screening was done by taking blood culture samples before administration of antibiotics, serum samples for CRP and blood samples for platelet count. Result: A total of 270 newborns with suspected sepsis were included in the study. Blood culture positivity was seen in 27.7 (27/75) cases. About 32.9% (89/270) of the neonates with suspected sepsis and 61.3% (46/75) neonates with confirmed sepsis had raised CRP; 32.2% (87/270) neonates with suspected sepsis and 64% (48/75) with confirmed sepsis had decreased platelet count. Both an increase in CRP and a decrease in platelets were seen in 61.3% (46/75) of confirmed cases. Conclusion: In our study, both raised CRP and decreased platelet count were seen in around 60% of confirmed cases of sepsis. So, CRP titre and platelet count can be used as early, rapid diagnostic markers for confirmed sepsis.